Guerra e parto: uma análise antropológica sobre a humanização do nascimento em Belo Horizonte - Renata de Oliveira Braga dos Santos (2016)
The birth event has become a real battleground for women of different social backgrounds. The transformation of the delivery environment from the domestic and female conditions to the hospital and medical-centered insertion gradually removed women's autonomy in parturition processes, and had important consequences that resound in the current assistance and this history is resumed here. The work later focuses on the organization of childbirth care in Belo Horizonte and the conflicts between the technocratic model and the movement for the humanization of birth, aiming to characterize professional categories, institutions and care decisions in the city, based on the discourse of the interviewees by the search. The humanization movement is evaluated in its logic of action, in order to perceive characteristics that form it and collaborate to reiterate reified images of women and maternity, in addition to establishing a class differentiation in the reflection on the obstetric scenario.